2018
DOI: 10.1111/jmft.12345
|View full text |Cite
|
Sign up to set email alerts
|

The risk of Telling: A Dyadic Perspective on Romantic Partners’ Responses to Child Sexual Abuse Disclosure and Their Associations with Sexual and Relationship Satisfaction

Abstract: Among 70 community couples who reported childhood sexual abuse (CSA) and disclosure to their partner, this study examined associations between survivors' perception of partner responses to their disclosure, and both partners' sexual and relationship satisfaction. Participants completed self-report questionnaires online. Results of path analyses within an actor-partner interdependence model indicated that survivors' perceived partner responses of emotional support to disclosure were associated with their own an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…CSA survivors may, for example, be reluctant to disclose their abuse history to their partner. De Montigny Gauthier et al (2019) reported that relationship satisfaction was influenced by both positive and negative responses to the disclosure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CSA survivors may, for example, be reluctant to disclose their abuse history to their partner. De Montigny Gauthier et al (2019) reported that relationship satisfaction was influenced by both positive and negative responses to the disclosure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seeking help or support from the romantic partner was the predominant rationale for disclosing, though the suicidality also emerged through less intentional methods for some participants (Authors, 2021). Perceptions of partner responses to disclosures of other stigmatized identities, such as sexual abuse (de Montigny Gauthier et al, 2019; MacIntosh et al, 2016), have been explored in previous studies, as have the partner's experiences following disclosure of mental illness (Shpigelman et al, 2019).…”
Section: Disclosures About Suicidementioning
confidence: 99%
“…With amplified public recognition of sexual misconduct due to social movements (e.g., #MeToo, TIME'S UP) and mass media campaigns (e.g., It's On Us, No More), disclosures of sexual trauma have surfaced publicly and interpersonally. Scant work has focused on the experiences of adult survivors navigating disclosures with intimate partners (e.g., de Montigny Gauthier et al, 2019). Given that sexual experiences are perceived as a taboo topic (Rankin & Bustle, 2008), it is crucial to gain a clearer understanding as to how partners respond to disclosures of sexual trauma.…”
Section: Communicating a History Of Sexual Trauma: Partner Responses ...mentioning
confidence: 99%